A precarious peace? The threat of paramilitary violence to the peace process in Colombia. - Maher, David; Thomson, Andrew (Third World Quarterly, 2018)
This article provides an investigation into claims that paramilitary violence in Colombia can pose a threat to the peace agreement signed in 2016 between the Colombian government and the FARC rebels. These claims highlight the capacity for paramilitary groups to 'spoil' the peace deal. Hitherto, however, there is a lack of scholarly research to investigate the potential of paramilitary spoiling. Firstly, this article highlights the flaws in the government's perspective that paramilitarism no longer exists in Colombia. Instead, the government argues that Colombia is plagued by criminal bands (known as BACRIMs). Secondly, through fieldwork interviews and questionnaires conducted in FARC demobilisation camps, together with descriptive data analysed through a uniquely coded dataset on violence in western Colombia, this article supports claims that successor paramilitary groups represent a key spoiler threat to the current government-FARC peace process. On the one hand, the paramilitaries can represent a direct spoiler threat by, for instance, violently targeting demobilising FARC guerrillas. On the other hand, successor paramilitary groups represent a key indirect spoiler threat, as paramilitary violence is exacerbating the root causes of the conflict that the peace deal seeks to address, with negative implications for the prospects for peace.